Pengaruh Kualitas Pelayanan dan Digital Marketing terhadap Kepuasan Pelanggan pada PT. Tiki Jalur Nugraha Ekakurir Cabang Utama Banjarmasin - Muhammad Al Zulhijjah; Said Muhammad (BIMA: Jurnal Bisnis dan Manajemen, 2022)
This research is to determine the effect of service quality on customer satisfaction, the influence of digital marketing on customer satisfaction, as well as the effect of service quality and digital marketing together on customer satisfaction at PT. Tiki Jalur Nugraha Ekakurir Cabang Utama Banjarmasin (JNE). The method used in this study is quantitative descriptive. Respondents in this study were 100 people who used the services of an expedition from JNE. The data collection technique used is a questionnaire, data collected in analysis using descriptive analysis and quantitative analysis of multiple linear regression. The results showed that service quality had a positive and significant effect on customer satisfaction, then digital marketing also had a positive and significant effect on customer satisfaction, then simultaneously showed that service quality and digital marketing had a positive and significant effect on customer satisfaction. The results of the analysis of the coefficient of determination of service quality and digital marketing variables on customer satisfaction are 0.382 or 38.2%, which means 38.2% of customer satisfaction is influenced by the quality of service and digital marketing, while the remaining 61.8% is influenced by other variables that are not examined by the author.